Pharmacometrics Time-To-Event And Disease Progression Modelling Of Diabetic Nephropathy In Patients With Type ii Diabetes Mellitus In Malaysia - Aziz, Sohail (2024)
Diabetic nephropathy (DN) is a significant complication of type 2 diabetes mellitus (T2DM) and poses a considerable burden on healthcare systems worldwide. This study aims to develop pharmacometrics-based time-to-event (TTE) and disease progression (DP) models to gain insights into the factors influencing the progression and development of diabetic nephropathy in a cohort of Malaysian patients, while also analysing the differences in clinical characteristics between patients with and without diabetic nephropathy. The data were collected from two tertiary care hospitals, and the patients were followed for 7.2 years. Parametric TTE analysis was conducted using NONMEM software. The event was defined as the development of persistent proteinuria for three consecutive visits. Three baseline hazard models exponential, Gompertz, and Weibull hazard models were tested. For the baseline HbA1c and eGFR model, both linear and non-linear disease progression models were assessed. The linear model represents the simplest disease progression model utilized in this study, assuming a constant rate of change in disease status over time. Within-group differences in clinical parameters under various drug treatments were evaluated using the Wilcoxon signed-rank test, while between-group analyses were conducted using the Mann-Whitney U Test.